Practical radio engineering and telemetry for industry - Bailey, David (Telecommunications engineer) (Elsevier, 2003)
Instrumentation and control, and electrical power engineering are increasingly reliant on radio-based communication technology. This is a comprehensive book covering the essentials of telemetry and radio communications. It explains the principles of telemetry and radio communications, describes their application and equips you with the skills to analyse, specify and debug telemetry and radio communications systems. Key issues addressed in this book are: * how to design and install radio (wireless) links * apply latest satellite technologies to your telemetry system * how to design and install microwave links * troubleshoot telemetry communications problems * tips, tricks and traps with radio links A guide to the design, installation and utilization of radio applications in instrumentation and control, and electrical power engineering Explains the principles of telemetry and radio communications, describes their application and equips you with the skills to analyse, specify and debug telemetry and radio communications systems Addresses topical areas such as designing and installing wireless communications links, the application of satellite technologies in telemetry, microwave links, etc.